Study of 300 cases of breast cancer: Treated in two collectivized assistance centers. Preliminary communication - D'Auria, Agustín; Armand Ugón, Alfredo; Pacheco, Héctor; Stein, Ester; Garat, Eduardo; Varela, Juan; Pees, Graciela; Viola Alles, Alberto; Musé, Ignacio (Cirugía del Uruguay, 1986)
Analysis of 300 patients with mammary gland cancer as treated in two collectivized Medical Care Centres far outpatients, between 1976 and 1983. 79% of patients consulted al stages still admitting surgical intervention (22,69% at stage I and 56,83% al stage II). In such cases intervention consisted in radical mastectomy: 49,9% of cases; modified radical mastectomy: 28,9%; simple mastectomy: 11,4 % and minar procedures: 14,9%. There was no surgery in a 6% of patients. In a 7,4 % of patients, bilateral mammary gland cancer was observed during the period under study (4,06% concomitant; 3,38% successive). 11 was observed that the older the palient, the longer the period of survival free from the disease as well as a reduced rate of mortality. The percentage of local recidivation in modified radical mastectomies (10,5%) was not superior to the percentage in radical mastectomies (12,9%). Analysis of clínical evolution of these patients according to the stage of presentation of !he disease and the surgical procedure selected.